Reputation as Social Control in Present China: Use, Misuse, Abuse, and Bankruptcy. Issue 2 (21st January 2016) - ZHAO, Bo
Abstract: Although reputation in general plays an effective role in social control in human communal life, this does not seem to work well in present-day China. This article discusses why "reputation as social control" malfunctions in Chinese society in view of the widespread reputation bankruptcy in various professions. Starting with China's discredited milk industry, it analyses similar regulatory failures in the economic, judicial, academic, and political sectors, explaining the interplay between key institutions. It argues that such regulatory failures can largely be attributed to the use, misuse, and abuse of reputation as a means of social control by the Chinese Party State to maintain monopoly power in a much diversified society resulting from China's rapid economic development and globalization. Based on the analysis of the Chinese circumstances, this article is also meant to contribute to the study of reputation as social control in general.